Biodiversity effects of benthic ecosystem engineers on the spatial patterns of sediment CH4 concentration in an urban Neotropical coastal lagoon - Caliman,Adriano (2013)
AIM: Biodiversity of sediment bioturbators has been shown to be important for to the magnitude and stability of benthic-pelagic processes. However, no study to date has evaluated the importance of the biodiversity of benthic invertebrate bioturbators to the spatial patterns of sediment CH4 concentration ([CH4]). Here we conducted a laboratorial experiment to test the following predictions: (1) Bioturbator species richness will reduce the sediment [CH4]; (2) individual bioturbator species (i.e. species composition) will have different effects on sediment [CH4]; (3) and both the effects of bioturbator species richness and composition on sediment [CH4] will be dependent on sediment depth. METHODS: We manipulated the number and composition of three functional divergent benthic invertebrate bioturbators species that are widespread in South Atlantic coastal lagoons, in laboratorial sediment chambers containing the sediment and water of an urban impacted coastal lagoon RESULTS: Bioturbator species richness had no overall significant effect on sediment [CH4] when comparisons of sediment [CH4] were made among species richness levels. However, bioturbator species richness significantly reduced sediment [CH4] when species richness levels were compared to the control (defaunated treatments), but this effect was significant only at the deepest sediment layer. Furthermore, bioturbator species composition had significant, but distinct effects on the patterns of reduction in sediment [CH4], depending on the sediment depth and the bioturbator species. CONCLUSIONS: We conclude that both the number and composition of bioturbator species are important to determine the effects of benthic bioturbators on spatial patterns of sediment [CH4], but the strength of these effects depend on species traits that determine interspecific interactions strength across the sediment vertical niche space.